An Empirical Study on Cost Benefit Comparison and Pricing Model of Cloud Computing Data Center and Traditional IDC - Ruozhao Feng; Yunling Fan (Dianxin kexue)
The development of cloud computing technology and market demand gradually promote the products of cloud data center services.As a reference to traditional IDC business of telecom operators,the cost structure and investment returns of cloud data centers and traditional IDC were compared through empirical analysis,as the basis for constructing cost pricing model of cloud data center.